2017
DOI: 10.1007/s10803-017-3165-6
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Predictors of Young Adult Social Functioning in 22q11.2 Deletion Syndrome

Abstract: Background The primary objectives of the current prospective longitudinal study were to (a) describe social functioning outcomes and (b) identify childhood predictors of social functioning in young adults with 22q11.2 Deletion Syndrome (22q11.2DS). Method Childhood predictors of young adult social functioning were examined. Family environment and parental stress in adolescence were investigated as potential mediators between childhood variables and adult social functioning. Results Parent rated childhood i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 95 publications
(121 reference statements)
3
24
0
Order By: Relevance
“…In the present review, the social outcomes of individuals with 22q11DS were assessed by parent ratings in almost all included studies. At the same time, discrepancies regarding social outcomes in parent vs. teacher [ 71 ], or parent vs. child and sibling were observed in the group of participants with 22q11DS [ 72 ]. Therefore, it is questionable whether the parent-ratings of social outcomes are sensitive enough to observe a specific association with social cognition in individuals with 22q11DS.…”
Section: Discussionmentioning
confidence: 99%
“…In the present review, the social outcomes of individuals with 22q11DS were assessed by parent ratings in almost all included studies. At the same time, discrepancies regarding social outcomes in parent vs. teacher [ 71 ], or parent vs. child and sibling were observed in the group of participants with 22q11DS [ 72 ]. Therefore, it is questionable whether the parent-ratings of social outcomes are sensitive enough to observe a specific association with social cognition in individuals with 22q11DS.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, several cross-sectional studies which used a dimensional approach (by means of parent and teacher reports) have reported increased rates of clinical behavior problems: 25–60% of 4–18-year-old subjects with 22q11.2DS were rated clinical with predominantly social and attention problems [ 15 , 16 ] whereas slightly lower rates of clinical cases (24%) have been found among 1.5–3 year old children [ 17 ]. Moreover, young individuals with 22q11.2DS scored significantly higher for internalizing problems when compared to community controls, siblings, age and intelligence matched children with speech-language delays without a genetic cause or children with clefts [ 13 , 18 , 19 , 20 ]. Additionally, they presented with lower social skills than community controls and siblings [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, young individuals with 22q11.2DS scored significantly higher for internalizing problems when compared to community controls, siblings, age and intelligence matched children with speech-language delays without a genetic cause or children with clefts [ 13 , 18 , 19 , 20 ]. Additionally, they presented with lower social skills than community controls and siblings [ 20 ]. Cross-sectional studies have suggested an increase in behavior problems, especially internalizing problems, with age [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations